The time machine - Wells, H. G. (Herbert George), 1866-1946 ([Boston, Mass] : Heinle Cengage Learning, 2007)
The Time Traveller first steps out of his magnificent time transport machine in the year 802,700! He finds the Earth populated by a race of slender pacifists and decides to study this lush land of flower people before returning to his own age
Title from container
Keywords: Time travel -- Fiction; Space warfare -- Fiction